PEMETAAN LITERASI SAINS MAHASISWA CALON GURU SEKOLAH DASAR PADA ABAD KE-21: BUKTI EMPIRIS UNTUK PENGUATAN KOMPETENSI PEDAGOGIK - Armin Arif; Dyah Retno Indarti; Risqah Amaliah Kasman; Muhammad Fuad; Dewi Hartini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Scientific literacy is an essential 21st-century competency that must be possessed by pre-service elementary school teachers to support critical thinking, problem-solving, and evidence-based decision-making. This study aims to map the level of scientific literacy among pre-service elementary school teachers in the Basic Concepts of Biology course as a basis for strengthening their pedagogical competence. The study employed a descriptive quantitative approach involving 60 students from the Elementary School Teacher Education Program at Universitas Megarezky using a total sampling technique. The instrument used was a scientific literacy test covering three domains: explaining scientific phenomena, evaluating and designing scientific investigations, and interpreting data and scientific evidence. The data were analyzed using descriptive statistics in the form of mean scores and percentages. The results showed that students’ scientific literacy was at a moderate level, with an average score of 68.4. The highest score was found in the domain of interpreting data and scientific evidence (73.5), while the lowest was in evaluating and designing scientific investigations (58.6). These findings indicate the need to strengthen inquiry-based, contextual, and investigative learning to enhance the pedagogical competence of pre-service elementary school teachers